2017
DOI: 10.1098/rsos.171223
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying intermolecular interactions of ionic liquids using cohesive energy densities

Abstract: For ionic liquids (ILs), both the large number of possible cation + anion combinations and their ionic nature provide a unique challenge for understanding intermolecular interactions. Cohesive energy density, ced, is used to quantify the strength of intermolecular interactions for molecular liquids, and is determined using the enthalpy of vaporization. A critical analysis of the experimental challenges and data to obtain ced for ILs is provided. For ILs there are two methods to judge the strength of intermolec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
54
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 234 publications
(573 reference statements)
6
54
1
Order By: Relevance
“…As far as we are aware, this is the first reported observation of the [BF4]anion in negative mode MS after vaporization of an IL. 33 Overall, these observations confirm that at 500 K under these experimental conditions the vaporization of [C4C1Im][BF4] NIPs is the dominant process.…”
Section: Heating Thin Films Of [C4c1im][bf4]: In Situ Mass Spectrometsupporting
confidence: 75%
See 3 more Smart Citations
“…As far as we are aware, this is the first reported observation of the [BF4]anion in negative mode MS after vaporization of an IL. 33 Overall, these observations confirm that at 500 K under these experimental conditions the vaporization of [C4C1Im][BF4] NIPs is the dominant process.…”
Section: Heating Thin Films Of [C4c1im][bf4]: In Situ Mass Spectrometsupporting
confidence: 75%
“…Vaporization of the NIPs occurs at much lower temperatures than liquid phase TD. Therefore, it can also be concluded that for 27,33,34,40,60 indicating that Ea,TD for these two ILs are likely to be towards 200 kJ mol -1 .…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The anion is considered to be the significant factor influencing the properties of ILs [ 35 ]. 1-Alkyl-3-methylimidazolium-based ILs are widely used in sample preparation and compounds extraction from plant materials, thus, 1-Butyl-3-methylimidazolium-based ILs with the same concentrations but six different anions (Br − , Cl − , BF4 − , ClO 4 − , HSO 4 − and NO 3 − ) were used in UMASDE to identify the best IL anion [ 43 ]. The results ( figure 4 a ) show that the yields of both EOs and the four flavonoids obtained using [C 4 mim]Br was higher than those obtained using other ILs.…”
Section: Resultsmentioning
confidence: 99%